STUDY OF SOME PATHOLOGICAL CHANGES IN MICE GROUPS INDUCED BY MYCOBACTERIUM TUBERCULOSIS AND TREATED WITH ETHAMBUTOL - Suhair H. Al-kutbi (Basrah Journal of Veterinary Research)
The main objective of this study is to demonstrate the histopathological changes and the efficacy of ethambutol of treatment mice infected with mycobacterium tuberculosis. Thirty of white Swisrland mice is 6-8 weeks age, weighted 20-25gm were used they were randomly divided into 3 groups contain of 10 animals for each group. - The 1st group (infected animal group) were inoculate.ed with 0.1 ml of bacterial suspension contain 1x108 cfu/ml intraperitonialy. - The 2nd group (group of infected-treated animal) were also infected as the fist group but after 30 day of infection were treated with 0.1 ml of ethambutol was given orally for 1 30 days. - The 3rd group maintained as a control and were inoculated with 1 ml of sterial normal saline intraperitonealy. At 60 day post infection all animals were sacrified and samples from different organs (liver, lungs, kidncys, spleen, intestine) were isolated for that histopathological examination. The result showed sever pathological lesion such as granulomatous lesions in lungs and livers of infected animals, with depletion of white pulp of spleen and conjestion with degenerative changes seen in kidneys and intestine with infiltration of inflammatory cells. While the infected-treated animals show mild or no pathological lesion in their internal organs.